2020
DOI: 10.1002/admt.201901122
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry Using Organic Optoelectronics under Ambient Light

Abstract: Light absorption in oxygenated and deoxygenated blood varies appreciably over the visible and nearinfrared spectrum. Pulse oximeters use two distinct wavelengths of light to measure oxygen saturation SpO 2 of blood. Currently, light-emitting diodes (LEDs) are used in oximeters, which need additional components to drive them and negatively impact the overall size of the sensor. In this work, we demonstrate an ambient light oximeter (ALO), which can measure photoplethysmography signals and SpO 2 using various ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…Soft and stretchable optoelectronics sensing for transmissive PPG measurement was demonstrated by Biswas, et al [ 83 ]. An interesting approach not requiring an LED but rather using ambient light for PPG sensing was demonstrated by Han, et al; with this approach, PPG signals with distinguishable heartbeat peaks were recorded and corresponding pulse oximetry readings were obtained [ 84 ].…”
Section: Current Sensor Technologymentioning
confidence: 99%
“…Soft and stretchable optoelectronics sensing for transmissive PPG measurement was demonstrated by Biswas, et al [ 83 ]. An interesting approach not requiring an LED but rather using ambient light for PPG sensing was demonstrated by Han, et al; with this approach, PPG signals with distinguishable heartbeat peaks were recorded and corresponding pulse oximetry readings were obtained [ 84 ].…”
Section: Current Sensor Technologymentioning
confidence: 99%
“…More recently, an ambient light oximeter (ALO), which works without the need for LEDs, was reported. [230] Two OPDs were utilized; the first a PCDTBT:PC 71 BM BHJ blend, and the second a P3HT:O-IDTBR BHJ blend. The ALO displays the potential to overcome the issues associated with devices that make use of a single OPD with two colored LEDs, since the power consumption of an ambient light oximeter is lower and it does not need the same level of optoelectronic driving hardware.…”
Section: The Bulk Heterojunction In Organic Photodetectorsmentioning
confidence: 99%
“…Reproduced with permission. [134] Copyright 2020, Wiley-VCH. d) High accuracy reflectance PPG sensor based on 16 × 16 OPD pixels and a LED array.…”
Section: Photoplethysmography (Ppg) Sensorsmentioning
confidence: 99%
“…Very recently, Han et al reported a novel approach to achieving pulse oximetry through combining the spectral filters covered PD‐OPDs and the ambient light as source, circumventing the use of LEDs. [ 134 ] The poly[ N ‐9″‐hepta‐decanyl‐2,7‐carbazole‐ alt ‐5,5‐(4′,7′‐di‐2‐thienyl‐2′,1′,3′‐benzothiadiazole)] (PCDTBT):PC 71 BM blends or P3HT:((5Z,5′Z)‐5,5′‐(((4,4,9,9‐tetraoctyl‐4,9‐dihydro‐ s ‐indaceno [1,2‐b:5,6‐b′]‐dithiophene‐2,7‐diyl) bis(benzo[ c ][1,2,5]thiadiazole‐7,4‐diyl))bis(methanylylidene))bis(3‐ethyl‐2‐thioxothiazolidin‐4‐one)) (O‐IDTBR) blends was employed as active layer, which enabled the PD‐OPDs to detect green, red, and NIR light. The PD‐OPDs were printed on the flexible substrates by blade coating technique, which can be well fitted with human body, such as fingers.…”
Section: Applications Of Broadband Organic Photodetectors In Sensorsmentioning
confidence: 99%